Distribution of magnetic nanoparticles in spherical polyelectrolyte brushes as observed by small‐angle X‐ray scattering. Issue 24 (8th September 2014) - Wang, Weihua; Li, Li; Yu, Xuanji; Han, Haoya; Guo, Xuhong
ABSTRACT Magnetic nanoparticles (MNPs) with a size of about 2 nm are prepared in nanoreactors of spherical polyelectrolyte brushes (SPBs) consisting of a solid polystyrene (PS) core and a shell of linear poly(acrylic acid) (PAA) chains densely grafted onto the core by one end. The synthesized MNP are strongly adhered to PAA chains due to the intense interaction of chemical coordination with the carboxyl groups. The generation of MNP in SPB layer is legibly revealed by small‐angle X‐ray scattering (SAXS) due to the significant increase in electron density. The radial distribution of MNP in SPB is built by fitting SAXS data. Most of MNP are found to locate nearby the surface of PS core. Compared to dynamic light scattering and transmission electron microscopy, SAXS can observe the generation and distribution of MNP in SPB as well as the changes upon changing pH and salt concentration in real time. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2014, 52, 1681–1688